Review on articles titled 'Challenging Aims in Management Teacher Training' and ‘Preparing Teachers and Experts for Discipline of Management: (Original title of the paper in Russian: Подготовка специалистов и преподавателей по дисциплине 'Мехеджмент') by Katalin, Hajdicsne Varga (Training and Practice : Journal of Educational Sciences, 2011)
Katalin Hajdicsne Varga describes the recent situation of so called management teacher training in her two papers in English and Russian, which is a special field of teacher education, from points of view of its development, history and from the point of view of its specific features, as well. [Published in H. Varga Katalin (2011): Beszéd- és szövegrögzítés. Töréteneti áttekintés és helyzetkép. Kaposvár, pp 87–98.]